Exercise alarms the immune system: A HMGB1 perspective. (October 2018) - Goh, Jorming; Behringer, Michael
Highlights: HMGB1 is an alarmin that responds to cellular stress or damage by modulating the inflammatory response. HMGB1 released from cells into systemic circulation during intense exercise may recruit macrophages and myogenic stem cells into skeletal muscle for tissue regeneration. Adaptation to exercise training can modulate circulating HMGB1 and suggests its utility as a biomarker in both healthy and clinical conditions. Abstract: The "danger" model of immunology states that the immune system detects and responds to danger by releasing endogenous molecules called alarmins. Strenuous exercise perturbs physiological homeostasis, increasing circulating alarmins to drive the inflammatory response. We describe a working concept of exercise-induced High Mobility Group Box (HMGB)1, a prototypical alarmin, in modulating immune responses and adaptations.